Sculpting ion channel functional expression with engineered ubiquitin ligases - Scott A Kanner (eLife, 2017)
The functional repertoire of surface ion channels is sustained by dynamic processes of trafficking, sorting, and degradation. Dysregulation of these processes underlies diverse ion channelopathies including cardiac arrhythmias and cystic fibrosis. Ubiquitination powerfully regulates multiple steps in the channel lifecycle, yet basic mechanistic understanding is confounded by promiscuity among E3 ligase/substrate interactions and ubiquitin code complexity. Here we targeted the catalytic domain of E3 ligase, CHIP, to YFP-tagged KCNQ1 ± KCNE1 subunits with a GFP-nanobody to selectively manipulate this channel complex in heterologous cells and adult rat cardiomyocytes. Engineered CHIP enhanced KCNQ1 ubiquitination, eliminated KCNQ1 surface-density, and abolished reconstituted K+ currents without affecting protein expression. A chemo-genetic variation enabling chemical control of ubiquitination revealed KCNQ1 surface-density declined with a ~ 3.5 hr t1/2 by impaired forward trafficking. The results illustrate utility of engineered E3 ligases to elucidate mechanisms underlying ubiquitin regulation of membrane proteins, and to achieve effective post-translational functional knockdown of ion channels.